Analysis of Mixed Convection inside an Enclosure in the Presence of a Rotating Grooved Cylinder - Rahim Hassanzadeh; Reza Rahimi; Vahideh Rahimi Hajifirouzi (Journal of Heat and Mass Transfer Research)
In the present study, mixed convective heat transfer inside a square enclosure in the presence of a rotating cylinder with various numbers of grooves is presented. Effects of counterclockwise and clockwise rotations with non-dimensional rotating speeds (RS) in the range from -1000 to 1000 are studied for different radius ratios (R) of 0.1, 0.2, and 0.3. Computations are carried out for Rayleigh numbers 103, 104, and 105 using the finite volume approach. The obtained results are validated against the available data for an empty enclosure (in the absence of a cylinder) as the reference case and also for an enclosure with a rotating smooth cylinder. It is demonstrated that for a specific value of the Rayleigh number, increasing the radius ratio enhances the thermal performance inside the enclosure regardless of the groove number and rotating speed. Increasing the Rayleigh number attenuates the roles of rotating speed and radius ratio, gradually. It is concluded that among all cases, the case with counterclockwise rotating smooth cylinder and among the grooved cases, Case 5 with three grooves provide the maximum heat transfer enhancements.